Improving relations between Islamists and non-Muslims in Malaysia : the case of Pan-Malaysian Islamic Party (PAS) - Mohd Izani Mohd Zain (Penerbit Universiti Kebangsaan Malaysia, 2018)
The constitution in PAS which stipulates that all of its members are to be Muslims have induced the party into an exclusive in nature. Nevertheless, in the attempts to increase the political supports within the nation, PAS needs cooperation from the non-Muslims. In this matter, PAS has established collaboration with the non-Muslims outside of the party through the establishment of Kelab Penyokong PAS (KPP, PAS Supporter Club) in 2004 which eventually upgraded into Dewan Himpunan Penyokong PAS (DHPP, PAS Supporter Assembly) in 2010. This paper will explain factors that induce the political collaboration between PAS with its non-Muslims’ supporters and to discuss the establishment of DHPP historically and contemporarily. These will also cover the issues as well as the challenges that echo the unique of political collaboration between PAS and non-Muslims. The findings of this writing show that political alliances helmed by PAS had successfully gained significant support from the non-Muslims. Nevertheless, PAS should give more attention to the issues arisen such as the equal status of memberships for the non-Muslims in the party as well as the level of their participations within the party, if PAS aspires to strengthen its alliances with the non-Muslims.